Growth and Inequality: A Meta-Analysis - Laura de Dominicis; Henri L.F. de Groot; Raymond J.G.M. Florax (Tinbergen Institute, 2006)
In recent years there has been a growing interest in the impact of inequality on economic growth. Both theoretical and empirical approaches have produced ambiguous results on sign and size of this relationship. Although there is a considerable part of the literature that considers inequality detrimental to growth, more recent studies have challenged this result and found a positive effect of inequality on growth. This paper contributes to the debate by using meta-analytical techniques to describe variation in observed outcomes of the empirical studies and to identify sources of variation.
Keywords: O11; O15; C42; C52; 330; growth; income distribution; inequality; meta-analysis